Maximal estimates for strong arithmetic means of Fourier series - Wilson Bobby (Advanced Nonlinear Studies)
It is well-understood that partial sums of Fourier series for L 1 functions don’t necessarily converge to the original function in the pointwise-almost everywhere sense. Estimates for averages of partial sum operators demonstrate that the divergence can be quantified. We establish a bilinear maximal estimate for averages of partial sums projectors.